Mechanisms of measles virus oncolytic immunotherapy - Pidelaserra Martí, Gemma; Engeland, Christine Elisabeth (Cytokine & growth factor reviews, 2020)
The study of measles virus (MeV) as a cancer immunotherapeutic was prompted by clinical observations of leukemia and lymphoma regressions in patients following measles virus infection in the 1970s and 1980s. Since then, numerous preclinical studies have confirmed the oncolytic activity of MeV vaccine strains as well as their potential to promote long-lasting tumor-specific immune responses. Early clinical data indicate that some of these effects may translate to the treatment of cancer patients. In this review, we provide a structured summary of current evidence for the anti-tumor immune activity of oncolytic MeV. We start with an overview of MeV oncolysis and MeV-induced immunogenic cell death. Next, we relate findings on MeV-mediated activation of antigen-presenting cells, T cell priming and effector mechanisms to the cancer immunity cycle. We discuss additional factors in the tumor microenvironment which are modulated by MeV treatment as well as the role of anti-viral immunity. Based on these findings, we highlight avenues for rational enhancement of oncolytic MeV immunotherapy by vector engineering. We further point to advantages and drawbacks of experimental models and propose areas warranting promising research. Lastly, we review the available immunomonitoring data from several Phase I clinical trials. While this review presents data for MeV, the concepts and principles introduced herein apply to other oncolytic viruses, providing a framework to assess novel cancer immunotherapies.